(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces the notion of quotient INK-algebra (X, *, 0). We formalize the notion of congruence relations in INK-Algebras, proving that the set of equivalence classes forms a partition. Additionally, we define a normal subset N of X and show that the quotient set X/N ={[x]_N|xX} where [x]_N={yX|xNy} and a binary operation on X/N such that [x]_N[y]_N=[x* y]_N for all [x]_N,[y]_NX/N forms a quotient INK-algebra.